Risk assessment of fine particulate matter exposure attributed to the presence of the cement industry - A. Mallongi; S. Stang; R.D.P. Astuti; A.U. Rauf; M.F. Natsir (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Chronic exposure to fine particulate matter may cause adverse health impacts on humans. The impact of  fine particulate matter  collected in the industrial area was explored. Therefore, this study aimed 1) to assess the levels and spatial distribution of fine particulate matter and 2) to estimate the health risks due to the exposure of fine particulate matter in the population surrounding the Maros cement industry.METHODS: Fine particulate matter measurement was carried out using direct reading HAZ-Dust Environmental Particulate Air Monitor  5000. This study used the Human Health Risk Assessment method from the United States Environmental Protection Agency to estimate health risks. The Monte Carlo Simulation model was used to estimate the uncertainty and sensitivity analysis of parameters.FINDINGS: The average fine particulate matter concentration was 23.68 micrograms per cubic meter, above the air quality guidelines of the World Health Organization. However, the Monte Carlo Simulation to assess the health risk with the 95th percentile demonstrated that children and adults are at low risk for developing adverse health effects. The result of sensitivity analysis showed that duration of exposure (27.0%) and concentration of fine particulate matter (25.7%) were the most contributing factors to health risks in adults and children, respectively. This new approach determines the critical factors with major effects on reducing the health risk of the vulnerable population.CONCLUSION: Fine particulate matter poses health risks to adults and children, despite the calculated risks are still acceptable. Thus, limiting exposure duration and maintaining fine particulate matter levels in the residential area are needed.